Spontaneous Tumor Lysis Syndrome in Blastoid-Variant Mantle Cell Lymphoma: Considerations for the General Internist. (July 2020) - Patel, Vishal; Case, Robert
Spontaneous tumor lysis syndrome (SPTLS) is a rare phenomenon that can manifest in rapidly proliferating hematological malignancies and solid tumors prior to initiating cytotoxic therapy. We encountered a patient who originally presented with diffuse lymphadenopathy, abdominal distention, and dyspnea, who had laboratory abnormalities suggestive of SPTLS. His peripheral flow cytometry and lymph node biopsy revealed blastoid-variant mantle cell lymphoma. Prior to initiating chemotherapy, acute kidney injury (AKI) and uric acid had improved with intravenous fluids and the initiation of allopurinol. However, after beginning chemotherapy, the patient developed a second AKI concerning for tumor lysis syndrome (TLS). He went on to have renal recovery and did not require renal replacement therapy. With the exception of case reports, there is limited evidence to guide general medicine clinicians who encounter cases of SPTLS. Expert-based guidelines are available to guide use of rasburicase, an uricase enzyme, before initiation of chemotherapy for certain malignancies when risk for TLS is considered high. Despite these guidelines, the role of rasburicase in preventing AKI remains controversial after inconclusive results in a meta-analysis. The causative relationship between uric acid and AKI in TLS is based on a mechanism of tubular obstruction. There are also mechanisms by which uric acid may cause AKI without tubular obstruction related to acute hyperuricemic nephropathy. Further characterization of the role of uric acid in causing AKI in patients without tubular obstruction may identify new mechanisms of injury and offer insight into new treatment strategies.